2016
DOI: 10.1007/s10493-016-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and distribution of Tuckerella japonica (Acari: Tuckerellidae) on tea bushes, Camellia sinensis and C. assamica, in Alabama, Georgia and South Carolina, USA

Abstract: Adults, immatures and eggs of Tuckerella japonica (Ehara) were collected from unknown clones or varieties of Camellia sinensis (L.) O. Kuntze tea bushes in the Clemson University Farm, Coastal Research and Education Center, Charleston, South Carolina; from Assam hybrids in The Caw Caw Nature Preserve in Ravenel, SC; from C. sinensis and C. assamica (Masters) in the Charleston Tea Plantation on Wadmalaw Island, SC; C. sinensis in the Fairhope Tea Plantation in Fairhope, Alabama; and from C. sinensis ‘Rosea’ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The locations of these punctures were in green periderm tissues exposed by longitudinally split bark on 1- to 3+-year-old woody stems. As 1-year-old stems increased in size, there was increased longitudinal splitting of the periderm with 2-year-old stems having the most bark splitting (Bond 1942 ; Childers et al 2016 ). Stylet lengths and diameters are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The locations of these punctures were in green periderm tissues exposed by longitudinally split bark on 1- to 3+-year-old woody stems. As 1-year-old stems increased in size, there was increased longitudinal splitting of the periderm with 2-year-old stems having the most bark splitting (Bond 1942 ; Childers et al 2016 ). Stylet lengths and diameters are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Tuckerella japonica has been observed feeding on exposed green periderm tissues in the crevasses created by splitting bark on 1- to 3+-year-old woody stems of tea [ Camellia sinensis (L.) O. Kuntze] (Childers et al 2016 ). With the descriptions of typical injury and recovery patterns caused by the above groups of mites in mind, this study was designed to examine the crevasses in which T. japonica was found to define the type of injuries to underlying tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Areas of bark splitting on C. sinensis stems were shown to be the preferred habitat of T. japonica infesting C. sinensis bushes (Childers et al 2016 ). Collyer ( 1969 ) reported Tuckerella flabellifera Miller favored rough areas and wounds on young wood and branches of its host plants with oviposition also observed at these locations.…”
Section: Resultsmentioning
confidence: 99%
“…Childers et al ( 2016 ) found T. japonica on the green periderm tissue that becomes exposed when the bark splits on stems of C. sinensis . Plants produced from both seed or unknown tea cultivars were included in the study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation